Perceptions about Healthy Eating and Emotional Factors Conditioning Eating Behaviour: A Study Involving Portugal, Brazil and Argentina - Cardoso, Ana Paula (2020)
This study analysed the perceptions about healthy eating as well as some emotional factors conditioning eating behaviour in a sample of people from Portugal, Brazil and Argentina. This is a descriptive cross-sectional study involving a non-probabilistic sample of 2501 participant. Data was collected through a questionnaire applied to adult citizens residing in their respective countries. For data analysis chi-square tests were used, and associations were evaluated by Cramer’s coeﬃcients. Moreover, a tree classiﬁcation analysis was conducted for variables related with perceptions about healthy eating and emotional conditioning of eating behaviour. The results revealed that participants’ perceptions are generally in agreement with healthy eating. However, signiﬁcant diﬀerences were found between countries (p = 0.018) and by levels of education (p < 0.0005), with a more accurate perception for Portugal and at the university level. The existence of statistically signiﬁcant associations between all sociodemographic variables considered and the conditioning of eating behaviour by emotional motivations should be noted. Tree classiﬁcation analysis showed that the most important discriminant sociodemographic variable for perceptions about healthy eating was education, followed by professional area and country, while the most relevant discriminants for emotional conditioning of eating behaviour were country and then living environment and sex. Thus, it is important to consider these variables in initiatives that aim to promote adherence to behaviours that contribute to the health and well-being of the population.